Novel KCNQ3 Mutation in a Large Family with Benign Familial Neonatal Epilepsy: A Rare Cause of Neonatal Seizures - Maljevic, Snezana (Mol Syndromol, 2016)
Benign familial neonatal seizures (BFNS) present a rare familial epilepsy syndrome caused by genetic alterations in the voltage-gated potassium channels Kv7.2 and Kv7.3, encoded by KCNQ2 and KCNQ3. While most BFNS families carry alterations in KCNQ2, mutations in KCNQ3 appear to be less common. Here, we describe a family with 6 individuals presenting with neonatal focal and generalized seizures. Genetic testing revealed a novel KCNQ3 variant, c.835G>T, cosegregating with seizures in 4 tested individuals. This variant results in a substitution of the highly conserved amino acid valine localized within the pore-forming transmembrane segment S5 (p.V279F). Functional investigations in Xenopus laevis oocytes revealed a loss of function, which supports p.V279F as a pathogenic mutation. When p.V279F was coexpressed with the wild-type (WT) Kv7.2 subunits, the resulting potassium currents were about 10-fold reduced compared to the WT Kv7.3 and Kv7.2 coexpression. Genotype-phenotype correlation shows an incomplete penetrance of p.V279F. Response to antiepileptic treatment was variable, but evaluation of treatment response remained challenging due to the self-limiting character of the disease. The identification of the pathogenic variant helped to avoid unnecessary investigations in affected family members and allowed guided therapy.